Predictors of sciatic pain among concrete reinforcement workers and house painters--a five-year follow-up. - Riihimaki, H.; Wickström, Gustav; Hanninen, K.; Luopajarvi, T. (Scandinavian Journal of Work, Environment & Health, 1989)
In a study of the association of occupation and several other determinants with the occurrence of sciatic pain, 167 concrete reinforcement workers and 161 house painters were followed for five years. Base-line data were obtained with a questionnaire, an interview on back symptoms, a clinical examination, and a radiograph of the lumbar spine. Follow-up data on back symptoms were obtained with a postal questionnaire. Concrete reinforcement work was associated with an increase in the risk of sciatic pain, in both a cross-sectional and a prospective study. Reported back accidents contributed to the risk of sciatic pain. Previous history of back symptoms was the most powerful predictor of sciatic pain prospectively. Degenerative changes were related to sciatic pain in retrospect, but prospectively this relationship was weaker. Body height and history of stress episodes showed some association with sciatic pain; abdominal muscle strength, body mass index, and smoking did not; and back muscle strength was associated only retrospectively.